Control of Scabies in a Boarding School Using 5% Permethrin Applied on Lesion Only - Sungkar, Saleha; Wahdini, Sri; Kekalih, Aria; Rilanda, Risa; Angkasa, Hansen; Widaty, Sandra (ASEAN Journal of Community Engagement, 2022)
Scabies is one of the most neglected tropical skin diseases in Indonesia. It is usually found in overcrowded communities with poor hygiene. The gold standard for scabies treatment is the whole-body topical application of 5% permethrin cream. However, the treatment causes inconvenience and stickiness for a prolonged period. The modification of topical treatment by applying only to the lesion yielded results similar with whole-body topical application. We consider using this mode of treatment to control the disease in a boarding school. The study was conducted from June to August 2019. All students were examined by dermatologists, and individuals who were diagnosed with scabies were treated using 5% permethrin for 12 h before wash-off (week 0) applied on the lesion only and reapplied a week after. The evaluation was conducted on weeks 4 and 8 by observing scabies lesions. Local health cadres were also trained, and environmental interventions were also performed. A total of 75 participants were analyzed. Most lesions were found on predilection sites such as finger web spaces of the left (57.3%) and right (58.7%) hands, gluteal region (60%), and penis (40%). The cure rate (CR) was 83%–100% of the lesions in week 4, which increased to 95%–100% in week 8. The CR on week 8 compared with baseline was 94.7% (p < 0.001). A total of 23 cadres were trained, and from post-test, 84% of the cadres showed good knowledge of scabies management. This novel application of 5% permethrin cream on the lesion only is an effective alternative to the conventional whole-body topical application.